Primary peritoneal adenocarcinoma as content of an incarcerated umbilical hernia: A case-report and review of the literature. (2016) - Varga-Szabó, D.; Papadakis, M.; Pröpper, S.; Zirngibl, H.
Highlights: We report on a rare case of primary peritoneal carcinoma. During operation there was no sign of malignancy. The diagnosis of primary peritoneal carcinoma was made by routine histological examination. We recommend routine histological examination of resected tissue. An overview of the literature on primary peritoneal carcinoma is given. Abstract: Introduction: Umbilical hernia is a common finding in many cases, posing potentially life-threatening complications, such as incarceration or strangulation. The presence of malignancy in hernia sacs is, however, rather rare. Presentation of case: Here we report on a case of primary peritoneal adenocarcinoma found through histological examination of omental tissue, resected due to an incarcerated umbilical hernia of an 84-years-old woman. There was no macroscopic sign of malignancy during operation; only after routine examination of histological sections the diagnosis was found. Discussion: To our knowledge this is the first report of primary peritoneal cancer as content of an umbilical hernia. This is a rare neoplasm and histologically identical to epithelial ovarian carcinoma. For this reason, the diagnosis is usually based on the histological finding and exclusion of a primary ovarian tumor. Primary peritoneal cancer has a poor outcome in general. Early diagnosis is, therefore, essential for effective treatment. Conclusion: Histological analysis of resected hernia sac or content should be performed routinely to discover malignant diseases in the background of a hernia.